(untitled) (Bangladesh Journal of Zoology, 2010)
The present investigation deals with the effects of corn flour (varieties: NK-40, BARI-5, Khai-Vutta and Hera) on the growth and development of the red flour beetle Tribolium castaneum (Herbst). Corn flours produced lighter larvae, pupae and adults in comparison with the control (Wheat+yeast). Corn flours also significantly (P <0.001) lengthened the larval period. The lowest percentage of adults was obtained on Hera flour and the highest on control. There were significant reductions in pupation and adult emergence (%) of the beetle on corn flours. Hera produced the most detrimental effects on T. castaneum. Bangladesh J. Zool. 38(1): 71-75, 2010